(±)-Neonardochinone A, a pair of enantiomeric neoligans from Nardostachys chinensis with their anti-Alzheimer's disease activities. (October 2020) - Wu, Pei-Qian; Li, Bing; Yu, Yi-Fan; Zhao, Ye; Yu, Chun-Xue; Zhi, De-Juan; Qi, Feng-Ming; Su, Pan-Jie; Wang, Ru-Yue; Fei, Dong-Qing; Zhang, Zhan-Xin
Graphical abstract: Highlights: A pair of new enantiomeric neoligans, (± )-neonardochinone A (1 ) were isolated from Nardostachys chinensis . The structure elucidation and chiral HPLC separation of (± )-neonardochinone A (1 ) were described. The absolute configurations of (–)-neonardochinone A and (+)-neonardochinone A were deduced by calculated ECD method. Compound 1 showed a possible significant anti-AD activity. Abstract: A pair of new enantiomeric neoligans, (± )-neonardochinone A (1 ) were isolated from Nardostachys chinensis . The structure of 1 was determined by extensive spectroscopic analysis, containing IR, HRESIMS, NMR spectra and single crystal X-ray diffraction. The enantiomeric separation was finished by HPLC on a chiral column. The absolute configurations were assigned via comparison of their calculated and experimental ECD data. The anti-Alzheimer's disease (AD) activities of 1, 1a, and 1b were also evaluated using the Caenorhabditis elegans AD pathological model, respectively, and 1 had the highest anti-AD activity.